Evaluation Model for Passing and Shooting Skills of Futsal Female Players - Hussein Saleh Najem; Khalil Hamid Mohammed Ali; Alaa Flayyih Jawad (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in identifying the reality of the skillful performance of female playersin the middle Euphrates clubs in futsal football, as well as deriving standards and setting standards for theskillful performance of futsal female players.As for the research problem, through the researchers’ follow-up of most futsal tournaments for femaleplayers, they noticed a clear weakness in the skillful performance of this game and without the level ofambition, and this came as a result of selection based on the experience of the training process, and it maybe accompanied by randomness in choosing without relying on evaluation evidence that helps in selectingthe female athletes, which is what urged researchers to study this phenomenon and stand on its true realityand delve into this matter and find the correct scientific evidence based on the correct scientific foundationsfor the skills of passing and scoring in futsal football, which is a scientific attempt in order to contribute tothe Iraqi feminist sport.